2016
DOI: 10.1016/j.amepre.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Low Back Pain and Spine Surgery

Abstract: In the presence of comorbidities associated with mental health, sleep, obesity, tobacco use, and alcohol use, LBP shows increased risk of becoming chronic/recurrent and faster time to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…In line with other studies, negative social interactions and social relations were found to be related to sleep quality (Elfering et al, 2016;Pereira et al, 2016;Pereira, Meier and Elfering, 2013). The association of sleep problems and musculoskeletal pain was confirmed before in large epidemiologic studies (Aghayev et al, 2010); specifically with respect to back pain (Kardouni, Shing and Rhon, 2016;Shmagel, Foley and Ibrahim, 2016). Thereby, sleep problems may arise as a consequence of musculoskeletal pain (Aghayev et al, 2010), as pain is known to Note.…”
Section: Discussionsupporting
confidence: 67%
“…In line with other studies, negative social interactions and social relations were found to be related to sleep quality (Elfering et al, 2016;Pereira et al, 2016;Pereira, Meier and Elfering, 2013). The association of sleep problems and musculoskeletal pain was confirmed before in large epidemiologic studies (Aghayev et al, 2010); specifically with respect to back pain (Kardouni, Shing and Rhon, 2016;Shmagel, Foley and Ibrahim, 2016). Thereby, sleep problems may arise as a consequence of musculoskeletal pain (Aghayev et al, 2010), as pain is known to Note.…”
Section: Discussionsupporting
confidence: 67%
“…The current results show that 0.69% of LBP subjects (1,805 cases out of 130,089 subjects) underwent surgery during the observed period whereas a similarly conducted study in U.S. soldiers reported a surgery rate of 1.94% (7,446 cases out of 383,586 subjects) [ 46 ]. As widely known, spinal surgery rates vary greatly across countries and regions, although the prevalence of spinal disorders is similar worldwide [ 47 , 48 ], which may be explained by differences in medical service accessibility, economic development, clinician education, etc.…”
Section: Discussionmentioning
confidence: 76%
“…Evaluated comorbid conditions included tobacco use and alcohol abuse at any time prior to the minimally invasive decompression, and persistent opioid use for 1 year prior to the minimally invasive decompression. Tobacco use and alcohol abuse were considered to represent those patients who may be poor‐surgical candidates due to an increased risk of perioperative complications 18–20 . Persistent opioid use was considered to identify patients who may have altered pain perception and function, thus impacting the perceived success of a minimally invasive approach and increasing the likelihood of progression to surgical management 21,22 .…”
Section: Methodsmentioning
confidence: 99%
“…Tobacco use and alcohol abuse were considered to represent those patients who may be poor-surgical candidates due to an increased risk of perioperative complications. [18][19][20] Persistent opioid use was considered to identify patients who may have altered pain perception and function, thus impacting the perceived success of a minimally invasive approach and increasing the likelihood of progression to surgical management. 21,22 Certain spinal pathologies were also evaluated that may predispose patients for the failure of minimally invasive techniques or are associated with more severe stenosis, including lumbar spondylosis with myelopathy, lumbar spondylolisthesis, lumbar radiculopathy, and a history of prior surgical intervention (i.e., surgical decompression, hemilaminectomy, laminotomy, or laminectomy).…”
Section: Evaluated Comorbid Conditionsmentioning
confidence: 99%